FEASIBILITY OF THE THREE DIMENSIONS OF THE CROSSED ANGIOSPERMAE PLANT FOR XI GRADE STUDENTS - Nur Latifah, Nunung; Sholihah, Mar'atus; Puspita Anggraini, Dian (Universitas Islam Balitar, 2018)
This study aims to determine the feasibility of the three dimensional cross section of the stem of the Angiosperm plant. This type research is Research and Development (R&D) with a 4D development model that is limited to the development stage. This research through assessment by material experts, media and language with an average score of 82.6% with a very valid category. Assessment of teacher responses score of 86.1% with a very valid category. Assessment of student responses to limited scale trials was 92% with very good categories. Three dimensional cross section of Angiosperm plant stem is very valid for use in classroom learning activities